Alkali-Activated Hybrid Cement from Mineral Wool Fiber Waste and OPC (2023)
ABSTRACT: Cements to replace ordinary portland cement (OPC) are currently being studied due to the high environmental costs of OPC production. One viable alternative is alkali-activated cements, which can be made from pozzolanic materials such as stone wool fiber waste (SW). At present, SW is the most used insulation material in the world, and the disposal and recycling of it is an environmental challenge due to its fibrous nature and low density. In the present work, an alkali-activated cement (AAC) and an alkali-activated hybrid cement (AAHC) were obtained from the alkaline activation of SW. The unconfined compressive strength (UCS) of the AAC and AAHC obtained was evaluated. After 28 days of curing at room temperature, the maximum UCS reached was 6.7 MPa for samples without the addition of OPC and 12.3 MPa for those with the addition of OPC. In addition, alkaline reaction products were identified in all the combinations through XRD and SEM-EDS. The results are promising as they show a hybrid material obtained from an industrial waste product and has a reduced carbon footprint.